PELAKSANAAN MANAJEMEN BERBASIS SEKOLAH (MBS) DI MTsN BATUSANGKAR - Misra, Misra (AT-TALIM, 2013)
Target of which wish to be reached in this research is to depict execution of MBS in MTSN Batusangkar and explain its contribution to make-up of quality and quality education of madrasah and also explain supplementary factor and resistor met in its execution. Result of this research of meneggambarkan that execution of MBS in good enough MTSN Batusangkar. its Management system enough succeed to give contribution in improving student achievement and have appearance of good enough organization. As for supplementary factor in execution of MBS in MTSN Batusangkar besides society support and government which is high enough, also leadership which is kharismatik. While its resistor factor is student input which still lower, limitation of facilities and basic facilities learn which not yet adequate and also the source of fund from all less promising student old fellowCopyright © 2013 by Al-Talim All right reservedDOI: 10.15548/jt.v20i2.40